REQUIREMENTS, SPECIFIC FEATURES AND DIFFERENCES OF A COPYRIGHT CONTRACT FROM OTHER CONTRACTS (World Bulletin of Management and Law, 2025)
The article analyzes the civil-legal nature of the copyright agreement based on the legislation of the Republic of Uzbekistan. It talks about the legal nature, structure, form of the copyright agreement, as well as the rights and obligations of the parties to it. The article also discusses what requirements must be met by persons who have reached an agreement on concluding a copyright agreement.